A new Stenognathriopes (Collembola, Symphypleona, Bourletiellidae) from Brazilian coast - Zeppelini, Douglas; Da Silva, Diego Dias (Zootaxa, 2012)
The new species Stenognathriopes (Tenentiella) janssensi sp. nov. (Collembola, Bourletiellidae) is described from coastal vegetation. This is the second species named to the subgenus Tenentiella and can be diagnosed by presenting nine subsegments on Ant IV, large conical tenent hair and tibiotarsal setae coarsely dented. The new species significantly extends the distribution of the genus and subgenus southward from Mexico to Northeastern Brazil. A comparative table is provided to the species of the genus Stenognathriopes.